Understanding and harnessing triple-negative breast cancer-related microbiota in oncology - Devoy, Ciaran; Flores Bueso, Yensi; Tangney, Mark (Frontiers in Oncology, 2022)
Bacterial inhabitants of the body have the potential to play a role in various stages of cancer initiation, progression, and treatment. These bacteria may be distal to the primary tumour, such as gut microbiota, or local to the tissue, before or after tumour growth. Breast cancer is well studied in this context. Triple Negative Breast Cancer (TNBC) is more aggressive, has fewer treatment options than receptor-positive breast cancers, and tends to grow with an overall worse prognosis and higher rates of reoccurrence. An in-depth understanding of the bacterial influence on TNBC progression and treatment is therefore of high value. The Gut Microbiota (GM) can be involved in various stages of tumour progression. It may suppress carcinogenesis or promote it through the release of carcinogenic metabolites, sustenance of pro-inflammatory environments and/or the promotion of epigenetic changes in our genome. The GM can also mediate metastasis and reoccurrence through interactions with the immune system and can affect genome instability where host DNA damage has occurred. Furthermore, the GM composition has been recently found to influence chemotherapy, radiotherapy, and immunotherapy. Bacteria have also been found to reside in normal and malignant breast tissue. Several studies have now described the breast and breast tumour microbiome, with the tumour microbiota of TNBC having the least taxonomic diversity among all breast cancer types. The conditions of the tumour microenvironment (TME) - low O2, leaky vasculature and immune suppression - are supportive of tumour-selective bacterial growth, and this innate ability could enable their use as delivery agents for various therapeutics or as diagnostics. This review aims to examine the current knowledge on bacterial relevance to TNBC and potential uses while examining some of the remaining unanswered questions regarding mechanisms underpinning observed effects.